Dynamics of tropical–extratropical interactions and extreme precipitation events in Saudi Arabia in autumn, winter and spring. (2nd May 2016) - de Vries, A. J.; Feldstein, S. B.; Riemer, M.; Tyrlis, E.; Sprenger, M.; Baumgart, M.; Fnais, M.; Lelieveld, J.
Abstract: Extreme precipitation in the arid Middle East can cause flash floods with dramatic societal impacts. This study investigates the synoptic‐scale dynamics of three extreme precipitation events that occurred in Saudi Arabia in autumn, winter and spring. Using ERA‐Interim reanalysis, soundings and observational precipitation data, we study precipitation characteristics, the synoptic circulations, moisture transport pathways and forcing mechanisms for upward motion. All three cases involved strong tropical–extratropical interactions whereby midlatitude forcing instigated an incursion of tropical moisture over the Arabian Peninsula that fuelled the heavy rainfall. In each case, a midlatitude upper‐level trough, associated with anticyclonic Rossby wave breaking, intruded into the subtropics. The phase relationship between this trough and the tropical low‐level circulation was consistent with wave amplification through baroclinic growth. Eulerian and Lagrangian analyses reveal moisture transport from nearby and remote tropical regions, leading to above‐normal tropospheric moisture content over Saudi Arabia. The autumn case (November 2009) showed a transient midlatitude upper‐level trough that interacted with the climatological Red Sea Trough near the surface, being an 'Active Red Sea Trough' event. The winter case (January 2005) resembled tropical plume‐like characteristics and demonstrated the coupling of a midlatitude cyclone and the equatorial low‐pressure zone over Africa, an intensified subtropical jet stream, and pronounced moisture fluxes at middle and upper levels. The spring case (April–May 2013) involved a quasi‐stationary cut‐off low and persistent advection of low‐level moist air masses, partly from the south Indian Ocean through cross‐equatorial flow. The forcing of ascent was associated with low‐level moisture convergence and decreased static stability (autumn case), dynamical lifting (winter case), strong surface sensible heating (spring case), and orographic lifting (all cases), favouring the build‐up and release of potential instability. We discuss the three cases from a seasonal perspective and present a synthesis of their common key synoptic features.